INVESTIGATING THE EFFECT OF CANVA ON STUDENTS’ WRITING SKILLS - Audi Yundayani; Susilawati Susilawati; Chairunnisa Chairunnisa (English Review: Journal of English Education, 2019)
A growing number of language teaching studies have started to consider the role of technology in teaching writing. Moreover, recent work in English as a Foreign Language (EFL) class has highlighted the importance of introducing visual media in an effort to help students improve their writing skills. The present study aims at investigating the effect of Canva on students’ writing skills. To this end, forty-four Indonesian EFL students were selected and assigned randomly to two writing classes, namely control and experimental groups. Before the treatment, both groups had a pre-test. During the sessions of instruction, both classes were taught by adopting Communicative Language Teaching (CLT) approach. However, in the experimental group, in order to help students to explore their writing ideas, they were asked to use Canva as media of writing. After the treatment, both groups had a post-test. Then, the number of writing errors made by students from both groups were compared using ANCOVA. The results showed that students in the experimental group had a significantly lower number of writing errors compared to the control group, which confirmed the positive effect of Canva in improving students’ writing skills.